2019
DOI: 10.2166/wst.2020.007
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection behavior of a UV-treated wastewater system using constructed wetlands and the rate of reactivation of pathogenic microorganisms

Abstract: The use of constructed wetlands as a wastewater treatment system is a feasible solution for rural areas. However, these systems do not efficiently eliminate pathogenic microorganisms. Therefore, it is necessary to implement disinfection systems such as ultraviolet (UV) disinfection systems in constructed wetlands. To evaluate the behavior of a UV system, a pilot system of artificial wetlands connected to one such disinfection system was operated. The results show that when the total suspended solids (TSS) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…The effluents assessed in this study contain TC and FC concentrations of 7.6 × 10 5 and 1.9 × 10 4 MPN/100 mL. This is consistent with the findings of various authors, who state that CW systems are not designed for the removal of E. coli, coliforms, or helminth eggs [9,26,50]. Because bacteria require more than 10 3 cells to cause an infection [59], the fecal load present in the effluents can pose a health risk in any projected reuse without prior disinfection treatment [50,63].…”
Section: Behavior Of Microbiological Compounds In a Cw And Their Rela...supporting
confidence: 90%
See 1 more Smart Citation
“…The effluents assessed in this study contain TC and FC concentrations of 7.6 × 10 5 and 1.9 × 10 4 MPN/100 mL. This is consistent with the findings of various authors, who state that CW systems are not designed for the removal of E. coli, coliforms, or helminth eggs [9,26,50]. Because bacteria require more than 10 3 cells to cause an infection [59], the fecal load present in the effluents can pose a health risk in any projected reuse without prior disinfection treatment [50,63].…”
Section: Behavior Of Microbiological Compounds In a Cw And Their Rela...supporting
confidence: 90%
“…However, the biodegradation capacity of the influents could be decreased due to the presence of surfactants and low nutrient loads [12]. In addition, it has been reported that CWs are not efficient for pathogen removal and could trigger the spread of resistance into the environment [17,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, disinfection is required in some areas to fulfil certain directives, such as the Habitats Directive (92/43/EEC) and Bathing Water Directive (2006/7/EC). The level of disinfection of microorganism is insufficient in constructed wetlands (López et al 2019 ), which is why some authors propose the use of UV photolytic reactors (Azaizeh et al 2013 ; González et al 2019 ) and others the use of maturation lagoons (Tanner et al 2005 ; Russo et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Este proyecto se puso en marcha el año 2011 y se ha generado investigación con conclusiones muy relevantes, respecto de la materia orgánica los sistemas lograron una eficiencia de eliminación de materia orgánica entre 69-72%. Sin embargo, tienen una baja capacidad de eliminación de nutrientes con eficiencia de eliminación de nitrógeno total de 37-44% y de fósforo total de 19-29% y para la desinfección de aguas es necesario un sistema terciario(Araya et al, 2016, Andrés et al, 2018, Leiva et al, 2020, González et al, 2020, Carrillo et al, 2022. También juega un rol relevante si las plantas macrófitas…”
unclassified